Analisis Kewenangan Presiden dalam Pembentukan Peraturan Pemerintah Pengganti Undang-Undang (PERPPU) Berdasarkan Perspektif Konstitusi dan Teori Perundang-Undangan: Studi Kasus UU No. 6 Tahun 2023 tentang Penetapan PERPPU No. 2 Tahun 2022 - Chadijah, Siti; Hadi, Abdul (Indonesian Journal Publisher, 2024)
This study examines the President's authority to issue Government Regulations in Lieu of Laws (PERPPU) based on constitutional perspectives and statutory theory, particularly in light of Law No. 6 of 2023 regarding the stipulation of PERPPU No. 2 of 2022. According to Article 22 of the 1945 Constitution of the Republic of Indonesia, the President may enact PERPPU